2021
DOI: 10.14505//jemt.v12.2(50).08
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Problems of International Legal Regulation of Transboundary Pollution

Abstract: This article is a comprehensive study on problems of legal protection of the environment from transboundary environmental pollution in the Republic of Kazakhstan. The study of international and national legislation in the field of environmental protection from transboundary environmental pollution was carried out, ways to solve legal problems related to transboundary environmental pollution were studied and proposed, theoretical concepts and practical recommendations were developed to increase the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The object of our study was Kazakhstan, where historically there has been a variety of industrial activities with an environmental impact (Makhmetova et al, 2023). Heavy metal contamination in Kazakhstan, being the ninth largest country in the world in terms of territory (Aytzhanova, 2019), is caused primarily by a combination of natural factors and technogenic activities (Bekezhanov et al, 2021). There are many hazardous areas (occupying more than 60 thousand ha) in Kazakhstan's industrial zones that contaminate the soil.…”
Section: Research Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The object of our study was Kazakhstan, where historically there has been a variety of industrial activities with an environmental impact (Makhmetova et al, 2023). Heavy metal contamination in Kazakhstan, being the ninth largest country in the world in terms of territory (Aytzhanova, 2019), is caused primarily by a combination of natural factors and technogenic activities (Bekezhanov et al, 2021). There are many hazardous areas (occupying more than 60 thousand ha) in Kazakhstan's industrial zones that contaminate the soil.…”
Section: Research Problemmentioning
confidence: 99%
“…The greatest concerns are caused by heavy metal contamination of soil (Bekezhanov et al, 2021;Li et al, 2020), which explains the focus of our study. Technogenic soil contamination is caused by various heavy metals, especially copper (Cu), nickel (Ni), cadmium (Cd), zinc (Zn), chromium (Cr), and lead (Pb) (Hinojosa et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Plenty of issues related to the collaboration between the state and business remain a subject of debate (Kulanov et al, 2020). However, international experience has shown that such cooperation can be highly effective in achieving socio-economic goals (Bekezhanov et al, 2021;Sergeeva et al, 2023). In Kazakhstan, the emphasis is placed on establishing the institutional basis for the relations between the state and business, which involves creating effective forms of interaction that enable the achievement of strategic goals.…”
Section: Introductionmentioning
confidence: 99%
“…The law of sustainable development is complex and interdisciplinary. It cannot be reduced to international, environmental, social, and economic law since it is based on the principles of many legal branches and requires a comprehensive analysis (Bekezhanov et al, 2021). The definition of sustainable development as a new branch of law is relevant and innovative as the traditional approach to the ideas of sustainable development and respect for the environment is transformed into a completely new concept (Zhatkanbayeva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%